The katha chest - Chowdhury, Radhiah (Salaam Reads, an imprint of Simon & Schuster Books for Young Readers, 2022)
Asiya loves to visit Nanu's house and rummage through her katha chest filled with quilts that tell stories about the bold and brave women in Asiya's family.